The role of Lactobacillus plantarum in oral health: a review of current studies - Xinyan Huang; Jianhang Bao; Mingzhen Yang; Yingying Li; Youwen Liu; Yuankun Zhai (Journal of Oral Microbiology)
Background Oral non-communicable diseases, particularly dental caries and periodontal disease, impose a significant global health burden. The underlying microbial dysbiosis is a prominent factor, driving interest in strategies that promote a balanced oral microbiome. Lactobacillus plantarum, a gram-positive lactic acid bacterium known for its adaptability, has gained attention for its potential to enhance oral health. Recent studies have explored the use of probiotic L. plantarum in managing dental caries, periodontal disease, and apical periodontitis. However, a comprehensive review on its effects in this context is still lacking.Aims This narrative review evaluates current literature on L. plantarum’s role in promoting oral health and highlights areas for future research.Content In general, the utilization of L. plantarum in managing non-communicable biofilm-dependent oral diseases is promising, but additional investigations are warranted. Key areas for future study include: exploring its mechanisms of action, identifying optimal strains or strain combinations of L. plantarum, determining effective delivery methods and dosages, developing commercial antibacterial agents from L. plantarum, and addressing safety considerations related to its use in oral care.